2006
DOI: 10.1002/uog.2669
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate derived from color Doppler myocardial imaging for assessment of fetal cardiac function

Abstract: Objective Color Doppler myocardial imaging (CDMI) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 15 publications
4
35
0
2
Order By: Relevance
“…In line with other researchers we believe that it would be of great clinical interest to apply tissue Doppler (TD) echocardiography in fetal diagnostics [1,2] . Several studies have reported the feasibility of TD for assessing fetal cardiac function using both spectral TD [3][4][5] and color-coded tissue velocity imaging (TVI) [2,[6][7][8] .…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…In line with other researchers we believe that it would be of great clinical interest to apply tissue Doppler (TD) echocardiography in fetal diagnostics [1,2] . Several studies have reported the feasibility of TD for assessing fetal cardiac function using both spectral TD [3][4][5] and color-coded tissue velocity imaging (TVI) [2,[6][7][8] .…”
Section: Introductionsupporting
confidence: 80%
“…Previous studies have reported observed limitations regarding the occurrence of fetal and/or maternal movement [2,[23][24][25][26][27] and the importance of exact placement of the ROI for offline analysis [26,27] . As far as reproducibility is concerned this creates difficulties when considering the environmental changes between the exams and in placing the ROI in the exact same location between investigations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other color tissue Doppler studies reported about increasing annular velocities during gestation in normal fetuses placing the ROI in the RV free wall or annulus 14,15 . We think, that measurements of tissue velocities are highly dependent on region of interest placement (even close to the atrioventricular level), the basically undefined ROI size (in the literature this ranges between 1 and 3mm) and the different ultrasound machines with post-processing algorithms [14][15][16][17][18][19][20] . Therefore, published tissue velocities vary and cannot be used interchangeably.…”
Section: Copyright © 2017 Association For Prenatal Cardiology Developmentioning
confidence: 99%
“…Doppler sonography and speckle-tracking technologies have also been described for ventricular strain and myocardial performance index measurements. [32][33][34][35][36][37][38][39] …”
Section: G Complementary Imaging Strategies (Optional)mentioning
confidence: 99%